Organellar carbon metabolism is coordinated with distinct developmental phases of secondary xylem. Issue 4 (25th March 2019) - Pinard, Desré; Fierro, Ana Carolina; Marchal, Kathleen; Myburg, Alexander A.; Mizrachi, Eshchar
Summary: Subcellular compartmentation of plant biosynthetic pathways in the mitochondria and plastids requires coordinated regulation of nuclear encoded genes, and the role of these genes has been largely ignored by wood researchers. In this study, we constructed a targeted systems genetics coexpression network of xylogenesis in Eucalyptus using plastid and mitochondrial carbon metabolic genes and compared the resulting clusters to the aspen xylem developmental series. The constructed network clusters reveal the organization of transcriptional modules regulating subcellular metabolic functions in plastids and mitochondria. Overlapping genes between the plastid and mitochondrial networks implicate the common transcriptional regulation of carbon metabolism during xylem secondary growth. We show that the central processes of organellar carbon metabolism are distinctly coordinated across the developmental stages of wood formation and are specifically associated with primary growth and secondary cell wall deposition. We also demonstrate that, during xylogenesis, plastid‐targeted carbon metabolism is partially regulated by the central clock for carbon allocation towards primary and secondary xylem growth, and we discuss these networks in the context of previously established associations with wood‐related complex traits. This study provides a new resolution into the integration and transcriptional regulation of plastid‐ and mitochondrial‐localized carbon metabolism during xylogenesis.